CAUSES OF DEVELOPMENT OF ACUTE AND CHRONIC THROMBOCYTOPENIA IN CHILDREN OF IRKUTSK REGION - N. N. Martynovich; O. P. Tolmacheva; V. A. Khyshova (Acta Biomedica Scientifica)
Background. Immune thrombocytopenia in children is not a rare disease. Currently, this diagnosis is found in 2 times more often than 5-10 years ago. Acute immune thrombocytopenia is increasingly taking on a chronic course. Aims. At present, it is impossible to predict the outcome of the disease. But the chronic course of the disease significantly reduces the quality of life of children and their parents. The purpose of the study is to determine the likely causes of the development and chronicity of the disease. Materials and Methods. A retrospective analysis of 433 case histories of the cancer department of the Regional Children’s Hospital in Irkutsk was conducted. Statistical processing of the received data was carried out with the help of the Matlab program and statistical package “Statistica 6.0”. Results. The main trigger factor is ARVI and vaccination against poliomyelitis. Sensitization to herpes viruses can be a provoking factor in the development of the disease when re-encountering the virus. The brighter the clinic, the more children receive immunoglobulin treatment and the disease often ends with complete recovery. Children with minimal clinical manifestations are treated with hormones and more often the disease passes into a chronic form. Conclusion. If the child is discharged from the hospital with only a clinical improvement, then there is a greater likelihood of a chronic process.